2007
DOI: 10.1073/pnas.0611311104
|View full text |Cite
|
Sign up to set email alerts
|

DDB1 is essential for genomic stability in developing epidermis

Abstract: The mammalian epidermis is maintained by proliferation and differentiation of epidermal progenitor cells in a stereotyped developmental program. Here we report that tissue-specific deletion of the UV-damaged DNA-binding protein 1 (DDB1) in mouse epidermis led to dramatic accumulation of c-Jun and p21Cip1, arrest of cell cycle at G2/M, selective apoptosis of proliferating cells, and as a result, a nearly complete loss of the epidermis and hair follicles. Deletion of the p53 tumor suppressor gene partially rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 38 publications
5
59
0
Order By: Relevance
“…We previously reported that DDB1 is essential for survival of proliferating cells in mouse brain and skin, but dispensable for nondividing cells such as neurons (21,22). Although highly differentiated, hepatocytes can reenter cell cycle and self-renew in response to loss of liver mass.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that DDB1 is essential for survival of proliferating cells in mouse brain and skin, but dispensable for nondividing cells such as neurons (21,22). Although highly differentiated, hepatocytes can reenter cell cycle and self-renew in response to loss of liver mass.…”
Section: Resultsmentioning
confidence: 99%
“…TUNEL-positive apoptotic cells were detected in regenerating livers but became more abundant in livers repopulated with DDB1-expressing hepatocytes (Fig. 2D), suggesting that DDB1-depleted hepatocytes, unlike DDB1-depleted neuronal and epidermal progenitor cells (21,22), do not undergo immediate apoptotic death but can survive for a very long time, presumably to maintain liver structural integrity and metabolic functions. No tissue necrosis (on histologic examination) or cell senescence (based on senescent β-galactosidase staining) were found during the regenerative process.…”
Section: Ddb1-expressing Hepatocytes Replace Ddb1-deficient Hepatocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Cang et al recently showed that loss of DDB1 (which forms part of the Cul4A ubiquitin ligase core) from mouse brain, lens, or epidermis caused apoptosis in proliferating cells. 50,51 Similarities between these Cul4A-and DDB1-deficient phenotypes likely correspond with their encoded proteins being components of the same Cul4A ubiquitin ligases.…”
Section: Cul4a Is Essential and Deletion Causes Apoptosis 327mentioning
confidence: 99%
“…The finding that CUL-4 orthologs in Drosophila and humans also negatively regulate the stability of CDK inhibitors of the CIP/KIP family provides the possibility that the latter pathway is also conserved. [49][50][51][52] What is the Role of CDKs in Regulating DNA Replication in Metazoa?…”
Section: Elegans Cul-4 Independently Regulates Both Cdc-6 and Cdt-mentioning
confidence: 99%